2006
DOI: 10.1007/s00520-006-0093-y
|View full text |Cite
|
Sign up to set email alerts
|

Bringing palliative care to a Canadian cancer center: the palliative care program at Princess Margaret Hospital

Abstract: Centre was created to allow the rapid banking of metastatic tumors from end-of-life patients to enhance our understanding of tumor development. Research tissue sampling is done on consented patients as soon as possible after death, but may be delayed for 24 hours or more. The purpose of this study was to determine the effect of time between patient death and tissue processing on RNA integrity. Design: RNA integrity number (RIN) scores were determined for primary tumors, metastatic lesions and normal uninvolved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
55
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 22 publications
0
55
0
Order By: Relevance
“…12 The literature on outpatient palliative care is limited. Several studies have described the experience of providing these clinics, [13][14][15][16] and a small number report outcomes. 2,17,18 The best example is the study which showed that early referral of all patients with newly diagnosed advanced lung cancer improved outcomes, including survival.…”
Section: Discussionmentioning
confidence: 99%
“…12 The literature on outpatient palliative care is limited. Several studies have described the experience of providing these clinics, [13][14][15][16] and a small number report outcomes. 2,17,18 The best example is the study which showed that early referral of all patients with newly diagnosed advanced lung cancer improved outcomes, including survival.…”
Section: Discussionmentioning
confidence: 99%
“…A study of an acute 12-bed PCU (anticipated stay of less than 2 weeks) by Zimmermann et al found a WT of 0-3 days 7 , although patient turnover in this setting would be expected to be faster than that in a facility designated for longer stays and terminal care.…”
Section: Discussionmentioning
confidence: 99%
“…The authors suggested that patients may be able to manage their own care until the very final stages of their illness before requiring institutionalization 4 . In comparison, the mean LOS was 11 days at an acute PCU (designed predominately for acute symptom management) in Toronto, where the maximum LOS is set at 2 weeks 7 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are a number of academic centers with active palliative care programs, and for the sake of example, two of these (MD Anderson Cancer Center and Princess Margaret Hospital) have published their experience in bringing comprehensive palliative medicine care to their institutions. 11,12 Their programs include robust palliative care research, inpatient palliative care units, and active outpatient palliative care clinics.…”
Section: Establishment Of Palliative Medicine Programs At Major Cancementioning
confidence: 99%